Reliability of interference fit at restorating closure head of a turbocharger - G. V. Redreev; V. V. Evstifeev; A. N. Rusanov; Y. A. Evseev (Вестник СибАДИ)
There is presented a model of loading closure head of a turbocharger, restorated by repair bush with interference, allowing to predict the distribution of stresses in the material of the bush and closure head depending on the sizes of a junction, kind of a load on the bush and to determine tolerances on oversizes of bushes and closure heads to ensure the immobility of receiving junction as well as guarantee absence of cracking in a closure head, made of iron.